a ) \(4x^2+2x+1=\left(2x\right)^2+2\cdot2x\cdot\frac{1}{2}+\frac{1}{4}+\frac{3}{4}=\left(2x+\frac{1}{2}\right)^2+\frac{3}{4}>0\forall x\)
b ) \(x^2+3x+4=\left(x^2+2\cdot\frac{3}{2}\cdot x+\frac{9}{4}\right)+\frac{7}{4}=\left(x+\frac{3}{2}\right)^2+\frac{7}{4}>0\forall x\)
c ) \(9x^2+3x+5=\left(3x\right)^2+2\cdot3x\cdot\frac{1}{2}+\frac{1}{4}+\frac{19}{4}=\left(3x+\frac{1}{2}\right)^2+\frac{19}{4}>0\forall x\)
Ta có : 4x2 + 2x + 1
= (2x)2 + 2.2x.\(\frac{1}{2}\) + \(\frac{1}{2}+\frac{3}{4}\)
= (2x + \(\frac{1}{2}\))2 + \(\frac{3}{4}\)
Mà : (2x + \(\frac{1}{2}\))2 \(\ge0\forall x\)
=> (2x + \(\frac{1}{2}\))2 + \(\frac{3}{4}\) \(\ge\frac{3}{4}\forall x\)
Hay : (2x + \(\frac{1}{2}\))2 + \(\frac{3}{4}\) \(>0\forall x\)
Vậy 4x2 + 2x + 1 \(>0\forall x\)